ANALYSIS OF THE PATHOGENESIS OF Aeromonas hydrophila IN THE AFRICAN CATFISH, Clarias gariepinus AND INVOLVEMENT OF THE TNF-a IN RESPONSE TO THE INFECTION - Tatik Mufidah; Sukenda Sukenda; Widanarni Widanarni; Huda Salahudin Darusman; Angela Mariana Lusiastuti (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2022)
This research aimed to study the pathogenesis of Aeromonas hydrophila infection through two different routes of infection in African catfish and to find out the involvement of TNF-a in response to the infection. The experimental infection model was performed by clipping the caudal fin and immersing the fish in a medium with A. hydrophila and by intramuscular injection. Total plate count were used to investigate total and the distribution of A. hydrophila in the organs and TNF-a were observed using immune histochemistry. The results showed that the two types of infection were able to show typical A. hydrophila symptoms in experimental fish. Histological observation indicated that the two types of experimental infection resulted in systemic aeromoniasis infection. Total bacterial count results showed that A. hydrophila were detected three hours post-infection (hpi) in all organs, except for the kidney, in which detection started since hour 0, both in control and challenge fish. TNF-a were detected in all experimental fish and influenced by the number of bacteria, the function and tissue structure and of the organs. It can be concluded that artificial infection by clipping the caudal fin of Clarias gariepinus and immersing the fish in a medium with active A. hydrophila isolates cause systemic aeromoniasis infection in organs. Acute infection with Aeromonas hydrophila causes an increase in TNF-a production.